2023
DOI: 10.3311/ppci.21309
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on RC Beams Strengthened by NSM Using CFRP Reinforcements

Abstract: Near Surface Mounted (NSM) Carbon Fiber-Reinforced Polymer (CFRP) reinforcement technique to improve the flexural strength of reinforced concrete members has become increasingly attractive in recent years. In this study, the practical problem of concrete cover depth cutting limitation was investigated. Twelve specimens were tested by four-point bending until failure. Experimental parameters include concrete cover depth, CFRP reinforcement type, CFRP positioning, and stirrups status. Furthermore, a nonlinear FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Chen et al investigated the U-wrap CFRP technique [9,13,14] and found that the bond length of the CFRP in this technique was constrained by the crosssectional dimensions of the concrete structure [15,16]. In addition, Ammar et al introduced near-surface-mounted (NSM) technology to shear-strengthening research [17,18], which can effectively enhance the shear-carrying capacity and deformation capacity when structures fail [19,20]. However, when the CFRP ratio is too high, it may cause the failure mode of reinforced beams to change to concrete cover delamination, resulting in the premature failure of the specimens [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al investigated the U-wrap CFRP technique [9,13,14] and found that the bond length of the CFRP in this technique was constrained by the crosssectional dimensions of the concrete structure [15,16]. In addition, Ammar et al introduced near-surface-mounted (NSM) technology to shear-strengthening research [17,18], which can effectively enhance the shear-carrying capacity and deformation capacity when structures fail [19,20]. However, when the CFRP ratio is too high, it may cause the failure mode of reinforced beams to change to concrete cover delamination, resulting in the premature failure of the specimens [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…When columns exposed to earthquake effects are wrapped with fiber reinforced polymer, although there is no significant increase in lateral rigidity and lateral load capacity, there is an improvement in displacement capacities [6]. In recent years, many studies have been carried out on the methods of full carbon fiber reinforced polymer cladding on reinforced concrete columns and carbon fiber reinforced polymer cladding by partial wrapping [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%